Is research ethics regulation really killing people?. Issue 6 (6th April 2015) - Hunter, David
Summary: It has been argued that research ethics regulation is leading to loss of life by delaying life‐saving research. For example, Whitney and Schneider argue that the delays to the ISIS‐2 trial cost 6538 lives. This suggests that there are grounds for rejecting research ethics regulation. However, the methods adopted by critics are flawed because: ► they conflate regulatory delays with those due to genuine normative requirements that would be present even if the regulatory framework was not; and ► looking at the impact of regulation on a per‐project basis is the wrong metric, because it neglects all the unsuccessful research and because delaying specific projects does not reduce the overall research done by researchers. Research ethics regulation does not lead to substantial losses of life, but we have strong obligations to make it as efficient as possible.